Bench to bedside: Current advances in regenerative medicine. (December 2018) - Clarke, Gabriella; Harley, Peter; Hubber, Ella-Louise; Manea, Teodora; Manuelli, Luigi; Read, Emily; Watt, Fiona M
Abstract : Regenerative medicine is a diverse and rapidly evolving field, employing core expertise from biologists, engineers, and clinicians. Recently the field has made significant progress towards regenerating or replacing tissues lost to age, disease or injury. Current strategies include transplantation of adult or pluripotent stem cells to replace tissue or support tissue healing. Promising approaches for the future of regenerative medicine include stimulating endogenous stem cells for in situ repair, transplantation of organoids to repair minor tissue injury, and the use of interspecies chimerism to produce functional metabolic organs for transplantation. In our review we focus on these emerging strategies, paying particular attention to their current and prospective translational impacts and challenges.